A detailed investigation on thermal behaviour of slim floor beams with web openings at elevated temperatures. (25th June 2019) - Alam, Naveed; Nadjai, Ali; Vassart, Olivier; Hanus, Francois
Abstract : Purpose: In recent times, the use of steel sections with web openings has become common as slim floor beams because they offer a reduction in weight of the steelwork, accommodate services within the floor depth and provide the composite action. The composite action in these beams is achieved either through the concrete dowels or through concrete plugs. Though these web openings offer several benefits in slim floor beams, they induce the material discontinuity in the steel web, which may affect their shear capacity and/or thermal behaviour. The purpose of this study is to investigate the thermal behaviour of slim floor beams with web openings in fire. Design/methodology/approach: This research presents findings from experimental and analytical investigations conducted to study the thermal behaviour of slim floor beams with web openings in fire. For this purpose, an experimental investigation was conducted, which shows that the presence of web openings has a major influence on temperature development across the steel section as well as along the span of these beams. The behaviour of the tested slim floor beam is validated using finite element modelling. The validated finite element model is then used to conduct a sensitivity study to analyse the influence of different opening spacings, sizes and shapes on the thermal performance of slim floor beams in fire. Findings: Test results show that the presence of web openings has a major influence on temperature development across the steel section as well as along the span of these beams. Temperatures on the web below the openings are found to be higher as compared to those recorded on the adjacent solid steel web. It is also observed that temperatures on the steel web above the openings are lesser than those on the adjacent solid steel web. Parametric studies conducted using the verified analytical modelling methods show that different opening spacings, sizes and shapes have a variable impact on the thermal behaviour of slim floor beams in fire. Closely spaced and larger opening sizes were found to have a more severe influence on their thermal behaviour in fire as compared to widely spaced and smaller openings. It was also found that the behaviour of these beams is influenced by the shape of the openings with rectangular openings resulting in more severe thermal distributions as compared to circular openings. Originality/value: The findings from this research study are highly valuable as they contribute to the existing knowledge database. There is a lack of experimental and analytical investigation on performance of slim floor beams with web openings at elevated temperatures. The results and conclusions from this study will help in developing innovative designs for slim floor beams and will help in reducing the fire related risk associated with structures comprising of slim floor beams with web openings.